2021
DOI: 10.3390/jcm10071352
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Biomarkers of Musculoskeletal Health with High Discriminant Ability for Age and Gender

Abstract: A novel approach to ageing studies assessed the discriminatory ability of a combination of routine physical function tests and novel measures, notably muscle mechanical properties and thigh composition (ultrasound imaging) to classify healthy individuals according to age and gender. The cross-sectional study included 138 community-dwelling, self-reported healthy males and females (65 young, mean age ± SD = 25.7 ± 4.8 years; 73 older, 74.9 ± 5.9 years). Handgrip strength; quadriceps strength; respiratory peak f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Our results for the axSpA group are consistent with recent research that found that higher lumbar and cervical tone, stiffness and decrement, and lower relaxation and creep for axSpA patients compared to healthy controls [45] is possibly due to increased spinal stiffness associated with axSpA [17,19,43]. Furthermore, the lumbar tone, stiffness, and decrement of the current sLBP and healthy groups were similar to those reported in subjects with chronic LBP and healthy subjects, respectively [54]. On the contrary, our results showed higher tone and stiffness and lower relaxation and creep than those reported in other younger axSpA and healthy samples [17,53], probably due to the changes of the MMPs associated with age [44].…”
Section: Differences In Mmps Spinal Mobility Pain and Quality Of Life Between Groupssupporting
confidence: 91%
See 2 more Smart Citations
“…Our results for the axSpA group are consistent with recent research that found that higher lumbar and cervical tone, stiffness and decrement, and lower relaxation and creep for axSpA patients compared to healthy controls [45] is possibly due to increased spinal stiffness associated with axSpA [17,19,43]. Furthermore, the lumbar tone, stiffness, and decrement of the current sLBP and healthy groups were similar to those reported in subjects with chronic LBP and healthy subjects, respectively [54]. On the contrary, our results showed higher tone and stiffness and lower relaxation and creep than those reported in other younger axSpA and healthy samples [17,53], probably due to the changes of the MMPs associated with age [44].…”
Section: Differences In Mmps Spinal Mobility Pain and Quality Of Life Between Groupssupporting
confidence: 91%
“…One of the strengths of this study was the evaluation of cervical MMPs in patients with a main alteration at the lumbar level, as previously suggested [54]. On the other hand, it is necessary to emphasize the clinical applicability of this research.…”
Section: Strengths and Limitationsmentioning
confidence: 85%
See 1 more Smart Citation
“…The description of the MMPs collected by the MyotonPRO is reported elsewhere [ 38 ], and can be summarized as: frequency, characterizing muscle tension or tone in resting state (Hz); biomechanical properties, such as stiffness (N/m) and logarithmic decrement in the amplitude of oscillation (Ø), characterizing the inverse of the elasticity [ 39 , 40 ]; and viscoelastic properties, such as relaxation time of stress (ms), and creep (Deborah Number -De-) [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“… Yang et al, 2019 ). Therefore, certain viscoelastic characteristics can turn out to become a reliable and useful physical biomarker for diseases, such as cancer or others, and age-specific changes ( Agyapong-Badu et al, 2021 ; Efremov et al, 2020 ; K.; Park et al, 2019 ). All of which can be impacted by the viscoelastic characteristics of the tumor extracellular matrix scaffold or age-associated changes of the extracellular matrix scaffold.…”
Section: Application Of the Viscoelasticity On Cancermentioning
confidence: 99%